Date marks, valuation, and food waste: Three in-store "eggsperiments" - Alessio D'Amato; Timo Goeschl; Luisa Lorè; Mariangela Zoli (University of Heidelberg, Department of Economics, 2020)
We provide causal evidence on how date marking policies influence consumers' valuation of perishable food products through three consecutive research steps. In a preparatory in-store survey (n = 100), we identify perishable food items that can be experimentally manipulated to overcome core challenges for causal identification. A modified in-store multiple price list (MPL) experiment (n = 200) then tests consumers' valuation of perishable food of varying shelf-life (expiry date) in a two-by-two design that varies date mark type(use-by versus best-before) and information status while preventing free disposal censoring. We find that expiry dates affect consumer valuation, but not differences in date mark type. Educating consumers about date mark meaning turns out to be conducive to discarding potentially unsafe food, but not to preventing food waste. An attentiveness experiment (n = 160) tests whether these treatment effects plausibly result from the nature of consumers' knowledge and finds that the existing asymmetry in consumers' understanding of current date marks can explain the evidence from the modified MPL experiment.
urn:nbn:de:bsz:16-heidok-290475
Keywords: D12; C93; Q53; Q18; 330; date marking; food waste; consumer valuation; information-based policies; multiple price list experiment; in-store experiment